Freezing-resistant gel electrolyte for low-temperature metal fuel cell as well as preparation method and application of freezing-resistant gel electrolyte
By using ZnSO4 and sorbitol modified gel electrolytes in aluminum air batteries, the problem of freezing of traditional electrolytes in low-temperature environments is solved, and the efficient discharge performance of aluminum air batteries under low-temperature conditions is achieved.
Patent Information
- Application Number
- CN202411954021.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-05-02
AI Technical Summary
Traditional aqueous electrolytes are prone to freezing in low-temperature environments, which limits their adaptability under extreme conditions and cannot meet the needs of efficient and sustainable power supply in low-temperature environments.
A freeze-resistant gel electrolyte is used, which forms a dense dendritic skeleton and microporous structure by introducing ZnSO4 and sorbitol as additives to the polyacrylamide gel matrix, enhancing mechanical properties and freezing resistance.
It significantly improves the discharge performance of aluminum air batteries in low temperature environments, and can discharge stably at minus 20℃ for 100 minutes, meeting the application requirements in low temperature environments.
Smart Images

Figure CN119921035A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal fuel cells, and more specifically, to a cryoresistant gel electrolyte for low-temperature metal fuel cells and a preparation method and application thereof. Background Art
[0002] With the rapid consumption of energy resources and the intensification of environmental problems, it has become an urgent task to find safe and efficient energy storage technology. Aluminum air battery (AAB) has a high theoretical discharge voltage (2.7V), capacity density (2980mAh gal -1 ) and energy density (8100Wh gal -1 ), as well as its low cost and environmental protection characteristics, have attracted widespread attention, especially in the field of portable power sources. In aluminum-air batteries, the electrolyte is a core component, and its performance directly affects the electrochemical properties of the battery. With the continuous growth of energy storage demand and the emergence of diversified application scenarios (such as polar research, deep-sea exploration, high-altitude exploration, and aerospace), the adaptability of energy storage devices to extreme weather conditions has become particularly important. However, traditional aqueous electrolytes are prone to freezing at sub-zero temperatures, which limits their adaptability in low-temperature environments and cannot meet the needs of efficient and sustainable power supply under extreme conditions.
[0003] Compared with traditional liquid electrolytes, gel polymer electrolytes (GPEs) composed of an organic polymer framework and liquid electrolytes have advantages such as low leakage, good mechanical properties and excellent electrochemical properties. However, the mechanical properties of traditional hydrogels as battery electrolytes need to be further improved, and because the freezing point of water is relatively high, traditional hydrogels as battery electrolytes will inevitably freeze at sub-zero temperatures, which will limit ion mobility and the wettability of the electrolyte-electrode interface, thereby restricting the application of flexible devices in low-temperature environments.
[0004] That is, existing hydrogel electrolytes still have the problem of insufficient distortion and stretching ability. In addition, their high freezing point and low ion mobility limit their application potential in low-temperature aluminum-air batteries. Summary of the invention
[0005] In view of the problems existing in the prior art, one of the objects of the present invention is to provide a method for preparing a cryoresistant gel electrolyte for a low-temperature metal fuel cell. The cryoresistant gel electrolyte has good mechanical properties such as bendability and stretchability, and has a simple structure, does not require sealing, and has low cost. It can significantly improve the low-temperature discharge performance of aluminum-air batteries, which is conducive to promoting the practical application of flexible aluminum-air batteries at low temperatures.
[0006] To achieve the above object, the technical solution of the present invention is as follows:
[0007] A method for preparing a cryoresistant gel electrolyte for a low-temperature metal fuel cell comprises the following steps:
[0008] 1) dissolving acrylamide in water to obtain solution A;
[0009] 2) adding the crosslinking agent and the initiator to solution A and mixing them evenly to obtain solution B;
[0010] 3) adding ZnSO4 and sorbitol stepwise into solution B, mixing and stirring uniformly under nitrogen atmosphere and room temperature to obtain solution C;
[0011] 4) Pour solution C into a mold, dry it, let it stand, and then allow it to swell and absorb alkali.
[0012] Furthermore, in step 1), the mass concentration of acrylamide in solution A is 20-40%, preferably 30%. After acrylamide is dissolved in water, the solution is magnetically stirred at room temperature (25° C.) for 1-2 hours to obtain solution A.
[0013] Furthermore, in step 2), the crosslinking agent is at least one of N,N'-methylene polyacrylamide, N-hydroxymethyl acrylamide, hydroxyethyl methacrylate, and diacetone acrylamide; the present invention preferably uses N,N'-methylene polyacrylamide, and the initiator is at least one of potassium persulfate, sodium persulfate, ammonium persulfate, etc.
[0014] Furthermore, in step 3), in the solution C, the concentration of ZnSO4 is 0.15-0.25M, preferably 0.2M; the concentration of sorbitol is 0.02-0.06M, preferably 0.04M.
[0015] Furthermore, in step 3), the stirring time is 2-4 hours, the rotation speed is 200-400 r / min, and the stirring method is magnetic stirring.
[0016] Furthermore, in step 4), the drying temperature is 60° C., the standing time is 5-8 hours, preferably 6 hours; and the swelling and alkali absorption is specifically soaked in a 4-6M alkaline solution for swelling and alkali absorption for 5-10 hours.
[0017] The alkaline solution is a KOH solution with a concentration of 5 M, and the swelling and alkali absorption time is 7 hours.
[0018] A second object of the present invention is to provide a cryoresistant gel electrolyte for low-temperature metal fuel cells prepared by any of the above preparation methods.
[0019] The present invention also aims to provide application of the above-mentioned cryoresistant gel electrolyte in metal fuel cells.
[0020] Furthermore, the metal fuel cell is an aluminum-air battery.
[0021] Furthermore, the application is specifically the application of metal fuel cells in aluminum-air batteries at minus 10°C to minus 20°C.
[0022] Specifically, a conductive carbon cloth coated with a commercial Premetek 20% Pt / C catalyst can be used as a cathode, a high-purity aluminum plate can be used as an anode, and the prepared gel electrolyte can be used as an electrolyte.
[0023] The present invention also aims to provide a low-temperature metal fuel cell comprising the above-mentioned cryoresistant gel electrolyte.
[0024] The present invention provides a cryoresistant gel polymer electrolyte, which selects ZnSO as an additive with the best salting-out effect through the Hofmeister sequence. 2- Ions can polarize water molecules around polyacrylamide, induce polyacrylamide chains to aggregate and form a crystalline structure, serve as effective cross-linking points in the hydrogel network, and enhance the hydrogen bonding between polyacrylamide chains, thereby significantly improving its mechanical properties. At the same time, sorbitol molecules contain six hydroxyl groups, which can effectively bind water molecules through hydrogen bonds, destroy the interaction between water molecules, inhibit the formation of ice crystals and reduce the activity of water, showing excellent water retention. This water retention property provides a liquid-like environment for OH-transmission inside the gel, thereby improving the ion transmission rate. In addition, sorbitol can also form strong hydrogen bonds with the three-dimensional skeleton of polyacrylamide, further enhancing the mechanical properties of the gel, and adsorb on the surface of the aluminum anode, effectively slowing down the self-corrosion behavior of the aluminum anode. The electrochemical performance of aluminum-air batteries was significantly improved by adding ZnSO and sorbitol to the polyacrylamide gel electrolyte. At minus 20°C, the aluminum-air battery assembled using the gel electrolyte has a stable discharge platform voltage of about 1.14V, and can discharge continuously for 100 minutes, meeting the application requirements of aluminum-air batteries in low-temperature environments.
[0025] Compared with the prior art, the present invention has the following advantages:
[0026] (1) The present invention prepares a gel electrolyte by introducing ZnSO4 and sorbitol as additives to the polyacrylamide gel matrix. The prepared gel electrolyte has a dense dendritic skeleton, and uniformly sized microporous structures are regularly arranged between the skeletons. This structure lays the foundation for the excellent mechanical properties and ion conduction of the gel electrolyte, and the prepared gel electrolyte has the best tensile strength and elongation at break. The antifreeze ability is improved with the addition of sorbitol. The assembled flexible aluminum-air battery has a power density of 36.52mW cm -2At minus 20°C, the aluminum-air battery assembled with the gel electrolyte has a stable discharge platform voltage of about 1.14V and a continuous discharge of 100 minutes, which can meet the application requirements of low-temperature aluminum-air batteries.
[0027] (2) The low-temperature gel electrolyte of the present invention has a simple and easy-to-operate preparation process, uses low-cost raw materials, meets green environmental protection standards, can be mass-produced, and has good application prospects. The prepared gel electrolyte has a stable structure and excellent electrochemical properties under low temperature conditions. With the support of this electrolyte, the aluminum-air battery has a stable operating voltage and exhibits excellent low-temperature discharge performance, which is suitable for a variety of applications in low-temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The macroscopic morphology diagrams under different deformations of Example 1 of the present invention;
[0029] Figure 2 The SEM images of the gel electrolyte obtained in Example 1 of the present invention, wherein (a) is a cross-sectional view of the gel at 1000 times magnification; (b) is a cross-sectional view of the gel at 2000 times magnification;
[0030] Figure 3 The tensile test results of Example 1 of the present invention and Comparative Examples 1 and 2 are shown in FIG.
[0031] Figure 4 The open circuit voltage test diagram of Example 1 of the present invention and Comparative Examples 1 and 2;
[0032] Figure 5 The power density test diagrams of Example 1 of the present invention and Comparative Examples 1 and 2 are shown;
[0033] Figure 6 The constant current discharge curves of Example 1 of the present invention and Comparative Example 1 and Comparative Example 2 at -10°C;
[0034] Figure 7 The constant current discharge curves of Example 1 of the present invention and Comparative Example 1 and Comparative Example 2 at -20°C;
[0035] Figure 8 The X-ray diffraction patterns of Example 1 and Comparative Examples 1 and 2 of the present invention are shown in FIG.
[0036] Fig. 9 The Fourier transform infrared spectra of Example 1 and Comparative Examples 1 and 2 of the present invention are shown. DETAILED DESCRIPTION
[0037] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0038] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0039] Unless otherwise specified, the materials and reagents used in the present invention can be obtained from commercial products in the art.
[0040] Example 1
[0041] A method for preparing a gel electrolyte for a low-temperature metal fuel cell comprises the following steps:
[0042] Step 1: Weigh 3 g of acrylamide, slowly add acrylamide powder into 10 ml of deionized water, and quickly stir with a glass rod, then place it on a magnetic stirrer for stirring for 1 hour to obtain solution A;
[0043] Step 2: Weigh 1.5 mg of N,N'-methylene polyacrylamide and 30 mg of potassium persulfate, slowly add them to the prepared solution A, and stir magnetically for 1 hour to form a uniform mixed solution B;
[0044] Step 3: Weigh 0.32 g ZnSO4 powder, slowly add it to the prepared mixed solution B, then weigh 0.072 g sorbitol, slowly add it, and magnetically stir for 2-4 h in a nitrogen atmosphere at room temperature (25°C) at a speed of 300 r / min to obtain solution C;
[0045] Step 4: Pour the prepared solution C into a mold, place it in a constant temperature oven at 60° C., and let it stand for 6 hours to obtain a gel electrolyte.
[0046] Figure 1 The macroscopic morphology of Example 1 of the present invention under different deformations is shown. It can be seen from the figure that the gel electrolyte obtained in Example 1 can still be restored to its original intact state after folding, stretching and twisting without cracks and damage, which shows that the gel electrolyte has strong flexibility and is not easy to break, can meet the actual use requirements of flexible aluminum-air batteries, and is suitable for various application scenarios.
[0047] Figure 2The SEM image of the gel electrolyte prepared in this example shows that it has a dense dendritic skeleton, and uniformly sized microporous structures are regularly arranged between the skeletons; this structure lays the foundation for the excellent mechanical properties and ion conduction of the gel electrolyte.
[0048] Comparative Example 1
[0049] Comparative Example 1 provides a method without adding ZnSO4 and sorbitol, which is as follows:
[0050] Step 1: Weigh 3 g of acrylamide, slowly add acrylamide powder into 10 ml of deionized water, and quickly stir with a glass rod, then place it on a magnetic stirrer for stirring for 1 hour to obtain solution A;
[0051] Step 2: Weigh 1.5 mg of N,N'-methylene polyacrylamide and 30 mg of potassium persulfate, slowly add them to the prepared solution A, and stir magnetically for 1 hour to form a uniform mixed solution B;
[0052] Step 3: Pour the prepared solution B into a mold, place it in a constant temperature oven at 60° C., and let it stand for 6 hours to obtain a gel electrolyte without additives.
[0053] Comparative Example 2
[0054] Comparative Example 1 and Comparative Example 2 provide a method of adding ZnSO4 but not adding sorbitol, as follows:
[0055] Step 1: Weigh 3 g of acrylamide, slowly add acrylamide powder into 10 ml of deionized water, and quickly stir with a glass rod, then place it on a magnetic stirrer for stirring for 1 hour to obtain solution A;
[0056] Step 2: Weigh 1.5 mg of N,N'-methylene polyacrylamide and 30 mg of potassium persulfate, slowly add them to the prepared solution A, and stir magnetically for 1 hour to form a uniform mixed solution B;
[0057] Step 3: Weigh 0.32 g ZnSO4 powder, slowly add it to the prepared mixed solution B, and magnetically stir it in a nitrogen atmosphere at room temperature (25°C) for 2-4 hours at a speed of 300 r / min to obtain solution C;
[0058] Step 4: Pour the prepared solution C into a mold, place it in a constant temperature oven at 60° C., and let it stand for 6 hours to obtain a gel electrolyte containing a ZnSO4 additive.
[0059] Performance Test:
[0060] 1. Mechanical properties
[0061] The gel electrolytes prepared in Example 1 and Comparative Examples 1-2 were subjected to a tensile test. The specific test method was as follows: the prepared gel was cut into a dumbbell shape with a specification of 20 mm × 5 mm, and both ends were fixed on a texture analyzer (CTX). The tensile rate was set to 50 mm min -1 The maximum stress and strain of the hydrogel were tested at room temperature to evaluate the flexibility and deformation ability of the gel electrolyte.
[0062] The results are as follows Figure 3 As shown, it can be seen that the gel electrolyte prepared in Example 1 of the present invention has the best tensile strength and elongation at break, indicating that the gel electrolyte obtained by introducing ZnSO4 and sorbitol at the same time can significantly improve its mechanical properties.
[0063] 2. Battery application test
[0064] A typical embodiment of the present invention provides a method for preparing an aluminum-air battery, which is as follows:
[0065] Preparation of aluminum-air battery cathode: Weigh 10 mg of commercial Premetek 20% Pt / C and add it to 10 ml of a mixed solution consisting of deionized water: anhydrous ethanol: 5% Nafion solution = 2:2:1 (volume ratio). Place it in an ultrasonic cleaner and ultrasonicate for 1 h. Use a pipette to draw 200 μL of the solution and evenly coat it on a 1×1 cm -2 The product was prepared by placing the product on a square conductive carbon cloth and placing it on a heating platform at 50°C for 1 hour and drying it.
[0066] Preparation of aluminum-air battery anode: A 5 mm thick aluminum plate is polished using a single-disk stepless speed grinder, wherein the sandpapers used are 220#, 600#, and 1000#, respectively. The polished aluminum plate is rinsed with deionized water and anhydrous ethanol for 3 times each, and then dried with cold air from a hair dryer.
[0067] The gel electrolytes prepared in Example 1 and Comparative Examples 1-2 were cut into cylindrical gels with a thickness of 3 mm and a diameter of 16 mm, and assembled in a battery mold in the order of air cathode-gel electrolyte-aluminum anode to obtain an aluminum-air battery. The open circuit voltage of the aluminum-air battery was tested using a CHI760E electrochemical workstation with a scan rate of 10 mV s -1 The test time is 120s; the power density of the aluminum-air battery is tested with a scan rate of 10mV s -1 The low-temperature discharge performance of aluminum-air batteries was tested using the Blue Electric test system and a low-temperature constant temperature test chamber. The test current density was 1 mA cm -2 .
[0068] Figure 4 The open circuit voltage test diagrams of Example 1 of the present invention and Comparative Examples 1 and 2 are shown. The initial open circuit voltages of the aluminum-air batteries prepared in Comparative Examples 1 and 2 are approximately 1.49V and 1.51V, respectively, while the open circuit voltage of the aluminum-air battery assembled with the gel electrolyte of Example 1 is increased to 1.53V, and the overall trend of the open circuit voltage is stable, indicating that the gel electrolyte with ZnSO4 and sorbitol additives has a higher open circuit voltage.
[0069] Figure 5 The power density test diagrams of Example 1 and Comparative Examples 1 and 2 are shown. The power densities of the aluminum-air batteries prepared in Comparative Examples 1 and 2 are 17.53 mW cm -2 and 33.29 mW cm -2 The power of the aluminum-air battery assembled with the gel electrolyte of Example 1 with sorbitol was further increased to 36.52 mW cm -2 , further improving the electrochemical performance of the assembled flexible aluminum-air battery.
[0070] Figure 6 The constant current discharge curves of Example 1 of the present invention and Comparative Examples 1 and 2 at -10°C are shown. It can be seen from the figure that the aluminum-air battery prepared by the pure PAM gel electrolyte of Comparative Example 1 has a discharge time of only 108.8 min, and the aluminum-air battery prepared by Comparative Example 2 with the introduction of ZnSO4 additive has a discharge time of only 112.7 min, and both have no stable discharge voltage platform. However, the aluminum-air battery prepared by Example 1 with ZnSO4 and sorbitol additives has a discharge time increased to 273.0 min, and the voltage is maintained within the normal range.
[0071] Figure 7 The constant current discharge curves of Example 1 of the present invention and Comparative Examples 1 and 2 at -20°C are shown. It can be seen from the figure that the aluminum-air battery prepared by the pure PAM gel electrolyte of Comparative Example 1 cannot be discharged, and the aluminum-air battery prepared by Comparative Example 2 with the addition of ZnSO4 can be discharged normally for 12.2 minutes, but there is no stable discharge voltage platform, while the aluminum-air battery prepared by Example 1 with the introduction of ZnSO4 and sorbitol has a significantly increased discharge time of 99.8 minutes at -20°C, and has a relatively stable discharge voltage platform. This shows that the gel electrolyte with ZnSO4 and sorbitol additives effectively prolongs the discharge time of the aluminum-air battery at -20°C.
[0072] Figure 8The X-ray diffraction diagrams of Example 1 of the present invention and Comparative Examples 1 and 2 are shown. The pure PAM gel sample of Comparative Example 1 presents broad and diffuse amorphous diffraction peaks, and Example 1 after the introduction of ZnSO4 and sorbitol still presents broad and diffuse amorphous diffraction peaks, without changing the crystal structure, and maintaining the stability of the original PAM three-dimensional skeleton structure. This gel electrolyte is like a "sponge" with high water absorption capacity. After soaking, the electrolyte can penetrate into the gel, providing a fast channel for ion transmission.
[0073] Fig. 9 The Fourier infrared spectra of Example 1 of the present invention and Comparative Examples 1 and 2 are shown. In Example 1 and Comparative Examples 1 and 2, it can be observed that the infrared spectra at 3343 and 3230 cm -1 -NH2 stretching vibration peak, 1659cm -1 The C=O stretching peak at 1435 cm-1, the CH bending peak at 1435 cm-1, and the CO stretching peak at 1092 cm-1 are originally at 3300 cm-1. -1 The -OH stretching vibration peak in water at the position was submerged, proving the success of the AM polymerization reaction. The -NH2 stretching vibration peak and C=O peak in Example 1, in which sorbitol and potassium sulfate were introduced, slightly blue-shifted, which was due to the hydrogen bond interaction between sorbitol and PAM. At the same time, no new absorption peak was formed, proving that the addition of additives would not destroy the stability of the overall structure of the gel.
[0074] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0075] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A method for preparing a cryoresistant gel electrolyte for a low-temperature metal fuel cell, characterized in that: The following steps are involved: 1) dissolving acrylamide in water to obtain solution A; 2) adding the crosslinking agent and the initiator to solution A and mixing them evenly to obtain solution B; 3) adding ZnSO4 and sorbitol stepwise into solution B, mixing and stirring uniformly under nitrogen atmosphere and room temperature to obtain solution C; 4) Pour solution C into a mold, dry it, let it stand, and then allow it to swell and absorb alkali.
2. The method for preparing a cryoresistant gel electrolyte for a low-temperature metal fuel cell according to claim 1, characterized in that: In step 1), the mass concentration of acrylamide in solution A is 20-40%, preferably 30%. After acrylamide is dissolved in water, it is stirred at room temperature for 1-2 hours to obtain solution A.
3. The method for preparing a cryoresistant gel electrolyte for a low-temperature metal fuel cell according to claim 1, characterized in that: In step 2), the cross-linking agent is N,N'-methylene polyacrylamide, and the initiator is potassium persulfate.
4. The method for preparing a cryoresistant gel electrolyte for a low-temperature metal fuel cell according to claim 1, characterized in that: In step 3), in the solution C, the concentration of ZnSO4 is 0.15-0.25M, preferably 0.2M; the concentration of sorbitol is 0.02-0.06M, preferably 0.04M.
5. The method for preparing a cryoresistant gel electrolyte for a low-temperature metal fuel cell according to claim 1, characterized in that: In step 3), the stirring time is 2-4 hours, and the rotation speed is 200-400 r / min.
6. The method for preparing a cryoresistant gel electrolyte for a low-temperature metal fuel cell according to claim 1, characterized in that: In step 4), the drying temperature is 60° C., and the standing time is 5-8 hours, preferably 6 hours; the swelling and alkali absorption is specifically soaked in a 4-6M alkaline solution for swelling and alkali absorption for 5-10 hours.
7. A cryoresistant gel electrolyte for low-temperature metal fuel cells prepared by any one of the preparation methods of claims 1 to 6.
8. Use of the cryoresistant gel electrolyte according to claim 7 in a metal fuel cell.
9. The use according to claim 8, characterized in that: The metal fuel cell is an aluminum-air battery.
10. A low-temperature metal fuel cell, characterized in that: Contains the freeze-resistant gel electrolyte according to claim 7.
Citation Information
Patent Citations
Gel electrolyte for zinc ion battery and preparation method thereof
CN111740172A
Alkaline gel electrolyte for aluminum air battery as well as preparation method and application of alkaline gel electrolyte
CN118299729A
Gel electrolytic capacitor and method for manufacturing the same
JP2019062166A
Metal air battery
JP2021111574A
Hydrogel and method for producing same
US20180163004A1